ZnTe semiconductor-polymer gel composited electrolyte for conversion of solar energy - Wonchai Promnopas (2018)
Nanostructured cubic p-type ZnTe for dye sensitized solar cells (DSSCs) was synthesized from 1: 1 molar ratio of Zn: Te by 600 W and 900 W microwave plasma for 30 min. In this research, their green emissions were detected at the same wavelengths of 563 nm, the energy gap (Eg) at 2.24 eV, and three Raman shifts at 205, 410, and 620 cm-1. The nanocomposited electrolyte of quasisolid state ZnO-DSSCs was in correlation with the increase in the JSC, VOC, fill factor (ff), and efficiency (η) by increasing the wt% of ZnTe-GPE (gel polymer electrolyte) to an optimum value and decreased afterwards. The optimal ZnO-DSSC performance was achieved for 0.20 wt% ZnTe-GPE with the highest photoelectronic energy conversion efficiency at 174.7% with respect to that of the GPE without doping of p-type ZnTe. © 2014 Wonchai Promnopas et al.